Improving Osmia lignaria and O. cornifrons (Hymenoptera: Megachilidae) retention with preferred nest materials and attractant spray. (7th April 2022) - Pinilla‐Gallego, Mario S.; Rowe, Logan M.; Gibbs, Jason; Pitts‐Singer, Theresa L.; Isaacs, Rufus
Abstract: Mason bees (Megachilidae: Osmia ) are alternative managed pollinators with the potential to supplement pollination by honey bees in many crops. However, challenges for their management in orchards still remain. If nesting conditions are not optimal, females can show high dispersion rates, which decrease their economic viability at commercial scales. One way to improve female retention is by offering attractive nesting substrates. We tested the effect of several combinations of substrate materials and shelter types, as well as an attractant compound, on the retention and performance of Osmia lignaria and O . cornifrons females. We compared nesting in three types of shelter (blue and white plastic totes and brown pine plywood), with cardboard tubes of four different diameters (5–8 mm), reeds, and wood blocks as substrates at an experimental farm orchard. In a separate experiment with plywood shelters and 7‐mm cardboard tubes, we tested an attractant spray based on decanoic acid (patent number US 9301521B2), a compound isolated from O . lignaria cocoons and expected to encourage females to nest in artificial cavities. In both experiments, O. cornifrons showed higher female retention than O . lignaria . The combination of plywood shelters with reeds had the highest nesting for both species, although O . cornifrons also readily used cardboard tubes of 5–6 mm diameter. The attractant spray increased nesting by O. cornifrons, but not by O. lignaria . We also found a significant interaction between the effect of the attractant and the year of the experiment, indicating that weather and other environmental variables could affect the efficacy of the attractant. Together, our results suggest that using the right combination of shelters and substrates, as well as the attractant spray, is an effective strategy to increase Osmia female retention for orchard pollination.